A Review of Phase Change Materials as a Heat Storage Medium for Cooling Applications in the Built Environment - Usman Masood; Mahmoud Haggag; Ahmed Hassan; Mohammad Laghari (Buildings, 2023)
The air conditioning demand varies significantly in the hot and desert climates of the UAE due to diurnal temperature variation, seasonal shifts, and occupancy patterns. One of the challenges faced by the relatively higher energy-consuming UAE building stock is to optimize cooling capacity utilization and prevent excessive energy loss due to undesired cooling. A potential route to achieving such a goal involves cooling energy storage during low demand and releasing the stored cooling at peak demand times via thermal energy storage (TES). Latent heat thermal energy storage (LHTES) employing phase change materials (PCMs) provides impactful prospects for such a scheme, thus gaining tremendous attention from the scientific community. The primary goal of the current article is to provide a comprehensive state-of-the-art literature review on PCM-based TES for cooling applications to understand its efficacy, limitations, and future prospects. The article involves various applications, designs, and validations. The article emphasizes the importance of material innovations and heat transfer augmentation strategies to render this technology feasible for real-life integration into cooling systems.